NILAI PENDIDIKAN BERKARAKTER DALAM NOVEL HAFALAN SHOLAT DELISA KARYA TERE LIYE: KAJIAN SOSIOLOGI SASTRA - Wanispa, Eka; Hidajati, Enny (Jurnal Ilmiah Bina Edukasi, 2018)
This research type is descriptive research by using approach of sociology of literature. The object of this research is the values ​​of character education in this novel. The data in this study are words, sentences, and discourses contained in this novel. The source of data in this novel. Data collection is done by reading and writing techniques. This study aims to explain the values ​​of education contained in this novel.. The results obtained in this study are 13 points, namely: (1) religious values, (2) honest values, (3) discipline value, (4) hard work value, (5) creative value, (6) independent value, (7) ) the value of curiosity, (8) the value of appreciation, (9) friendly and communicative value, (10) the value of peace love, (11) the value of reading, (12) the value of social care, (13) the value of responsibility.